Estimating self‐clutter of the multiple‐pulse technique. Issue 7 (24th July 2015) - Reimer, A. S.; Hussey, G. C.
Abstract Autocorrelation function (ACF) estimates from voltage data measured by high‐frequency ionospheric radar systems that utilize the multiple‐pulse technique of Farley (1972) are susceptible to interference from self‐clutter. Self‐clutter is caused by simultaneous returns from multiple transmitted pulses echoing from unwanted, or ambiguous ranges. Without accurate estimates of self‐clutter it is impossible to account for all the uncertainty in estimates of the radar ACF. Voltage‐ and power‐based self‐clutter estimators are presented and evaluated using a modified version of the radar data simulator of Ribeiro et al. (2013a) and data from the Super Dual Auroral Radar Network (SuperDARN). It is shown that self‐clutter caused by ambiguous ranges filled with ground scatter can be accurately estimated using a voltage‐based self‐clutter estimator but that for ionospheric origin self‐clutter a maximal estimator must be used. Two maximal self‐clutter estimators are discussed and verified using the radar data simulator. A discussion of the application of the self‐clutter estimator as it is applied to ACFs obtained with Saskatoon SuperDARN radar is also presented.